Load Management System with Integration of Renewable Energy Resources - Rashid, Faizan; Gilany, Adeel; Rasheed, Saim; Nisar, Hamza; Raza, Ali; Hasnat, Muhammad (International Journal of Integrated Engineering, 2021)
This article presents, a load management system is designed and implemented to integrate renewable energy resources (RES) (solar and wind), which manage the load according to the supply/demand and the user’s priorities. The system is implemented on a hybrid system integrating wind energy, solar energy, utility supply, and battery energy storage system. Load management is carried out via switching of the loads. The sources can also be turned ON and OFF. During excess power, the battery module works as an energy storage unit or backup energy supply unit during demand. Loads can be turned ON and OFF wirelessly via GSM. The grid operator can switch the loads by simply sending a command via a short service message (SMS). In the end, the system is tested, and the results are presented. The hybrid system is simulated in MATLAB/Simulink first and then hardware implementation is carried out, which involves integrating renewable resources via converters and load management by switching using a microcontroller (Arduino).